Intracranial Aneurysms Treated with Guglielmi Detachable Coils: Usefulness of 6-Month Imaging Follow-Up with Contrast-Enhanced MR Angiography - Gauvrit, Jean-Yves (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: This study was undertaken to assess the utility of contrast-enhanced MR angiography at 6 months after endovascular treatment of intracranial aneurysms with Guglielmi detachable coils. METHODS: Contrast-enhanced MR angiography was performed in 47 patients at 6 and 12 months after endovascular treatment of intracranial aneurysms (48 aneurysms). Digital subtraction angiography (DSA) was used as reference and was performed at 12 months after the treatment in all patients. MR angiographs were analyzed independently by two senior radiologists. DSA and MR angiography findings were assigned into one of three categories: complete obliteration, residual neck, or residual aneurysm. RESULTS: All examinations were assessable. Interobserver agreement was judged as very good for contrast-enhanced MR angiography (κ = 0.96), with one discrepancy between examiners. Comparison between MR angiography at 6 months and DSA at 12 months showed an excellent agreement between techniques (κ = 0.93). Two cases of complete occlusion at DSA were misclassified as a residual neck at 6-month MR angiography. All aneurysm recanalizations at DSA already were detected on MR angiography at 6 months. The size of aneurysm recanalization did not increase between both MR angiographs performed at 6 and 12 months. CONCLUSION: Contrast-enhanced MR angiography after selective embolization of intracranial aneurysm seems to predict properly early aneurysm recanalizations.